Specialized processors for authentication of the interaction parties based on recurrent sequences - Яремчук, Юрій Євгенович (Ukrainian Information Security Research Journal, 2013)
In this work, we consider the mathematical apparatus of recurrent and sequences, as well as a possibility of constructing an authentication method for the parties, based on it. For the proposed method, we developed principles of specialized processors with a possibility for each party of interaction to prove and validate the authenticity. Comparison of the speed of the developed processors with the known analogues showed that, under certain conditions, the work time of the developed specialized authentication processors will be dozens of times less than the processors implementing the known methods. The developed specialized processors have a perspective to be used in various cryptographic tasks, based on the public key technology.